Decoupling Analysis of Water Resource Utilization and Economic Growth in Gansu Province Based on Water Footprint Theory - LIU Xian; YUAN Dan; HAN Yifei; TANG Jiaoyu; LU Yang (Renmin Zhujiang)
To explore the relationship between water resource utilization and coordinated economic development in Gansu Province,this study employs the statistical data of Gansu Province from 2008 to 2019 to analyze the trend of water footprints and evaluation indicators for water resources.Moreover,the decoupling evaluation model is used to evaluate the relationship between water resource utilization and economic growth.The results reveal that the water footprint and per capita water footprint of Gansu Province have shown an upward trend of parallel fluctuations for the past 12 years,in which the agricultural water footprint is the main component of water footprints,accounting for 86.78% on average,and the ecological water footprint increases year by year.The self-sufficiency rate of water resources remains above 90%,and the economic benefit of water resources increases from 20.11 yuan/m3 (in 2008) to 43.35 yuan/m3 (in 2019),with an average annual growth rate of 6.6%.The pressure index of water resources has had a downward trend in the past five years,which is in a state of water security on the whole.The relationship between GDP and water resource utilization is gradually changing from weak decoupling to strong decoupling,and that between agricultural output value and agricultural water use is changing from negative decoupling with unsatisfactory expansion to strong decoupling.On the basis of these conclusions,some suggestions on agriculture,import and export trade,and ecology are put forward to promote the high-quality coordinated development between water resource utilization and economic growth in Gansu Province.